Pengaruh Penggunaan Media Papan Tempel terhadap Hasil Membaca Permulaan Peserta Didik Kelas I pada Mata Pelajaran Bahasa Indonesia di SDK St. Yoseph 2 Kota Kupang - , Eltiana Odes; Hingrida Margarita Anastasia Hendrik; Tua, Siprianus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Early reading ability constitutes a fundamental literacy skill that influences students' subsequent academic development. However, many first-grade elementary school students continue to experience difficulties in letter recognition, syllable decoding, word identification, and simple sentence reading. This study aimed to examine the effect of bulletin board media on the early reading ability of first-grade students at SDK St. Yoseph 2 Kupang City. The research employed a pre-experimental method using a one-group pretest-posttest design. The study involved 25 first-grade students selected through total sampling. Data were collected using an early reading achievement test administered before and after the intervention. Data analysis included descriptive statistics, Shapiro-Wilk normality testing, paired sample t-test, and normalized gain (N-Gain) analysis. The descriptive results indicated an increase in students’ reading performance after the implementation of bulletin board media. The paired sample t-test revealed a significance value of 0.001 (p < 0.05), indicating a statistically significant difference between pretest and posttest scores. Furthermore, the N-Gain score reached 72.95%, which falls within the high effectiveness category. These findings demonstrate that bulletin board media contributes positively to the improvement of students’ early reading ability by facilitating letter recognition, syllable formation, word reading, and simple sentence comprehension. The study suggests that bulletin board media can serve as an effective, practical, and low-cost instructional medium for strengthening early literacy learning in elementary schools